In vitro selection and characterization of cadmium-tolerant calli of Tagetes erecta and Gomphrena globosa - Lama, Gauri; Shrestha, Bineeta; Limbu, Sunita; Gurung, Prithivi Raj; Pant, Krishna Kumar (Banko Janakari, 2024)
Ornamental plants (OPs) are beneficial to remove, control and reduce heavy metals (HMs) in a process called 'phytoremediation'. This study evaluated the in vitro system-based phytoremediation properties of Tagetes erecta and Gomphrena globosa calli. Leaves from in vitro seed-grown T. erecta and G. globosa were used as an explant source for callus culture. Callus culture was found optimal in MS medium supplemented with 8 μM BAP + NAA for T. erecta and 2 μ M 2, 4-D for G. globosa. These plants were grown in their respective optimized (controlled) medium enriched with different amounts (50, 100, 150, 200, and 250 μM) of Cadmium (Cd) added in the form of Cadmium chloride (CdCl2). The in vitro calli developed were evaluated for Cd stress tolerance based on callus diameter, growth tolerance index (GTI) and catalase (CAT) activity. Over four weeks, the callus diameters of T. erecta and G. globosa grown in different concentrations of Cd had lower growth than that of the controlled one. On the other hand, the GTI measured were greatest at 150 μM of Cd for both T. erecta (130.95%) and G. globosa (149.32%) suggesting a potential Cd tolerance. However, the CAT activity in T. erecta callus increased with the Cd concentration peaking at 150 µM then started declining while G. globosa callus showed the highest CAT activity at 50 μM of Cd. Thus, T. erecta callus showed greater Cd tolerance with the prospect of utilizing it for phytoremediation. The study also suggests growing T. erecta at 150 μM Cd for tolerant calli.